0336 Sleep Time and Risk Taking Behaviour in Night Shift-Workers. (25th May 2022) - Ravi, Anushree; Bryans, Helena; Ruprich, Melissa; Burgeess, Helen; Roth, Thomas; Drake, Christopher; Cheng, Philip
Abstract: Introduction: Night shift-workers are integral in a multitude of industries. Many night shift-workers experience sleep loss, which may impact their risk taking behaviour.This study aimed to identify the correlation between total sleep time (TST) and shift-workers' engagement in risk-taking behavior. Methods: 53 night shift-workers participated in the experiment. Polysomnography was conducted to determine the TST of shift-workers prior to completing a task that measured risk taking behaviour. This task simulated a driving scenario in which participants must decide whether or not to proceed at a yellow traffic light. Participants were not informed of the duration of the yellow light, which varied unpredictably in duration. The task consisted of 16 trials, and participants earned points that translated to a cash incentive (25 points = 25 cents). Participants either earned or lost 25 points depending on the success of each trial. Failure was defined as running a red light. Those who proceeded at every trial were categorized as insensitive to risk. Results: The data revealed that those insensitive to risk had a significantly lower TST value.Those insensitive to risk had a lower mean sleep time (374 minutes, SD=75) compared to those sensitive to risk (415 minutes, SD= 42), p =.01 (Cohen's d=0.67). Conclusion: Sleep time is associated with risk-taking behavior in night shift-workers. This study offers insight into the amplification of risk taking behaviours within night shift-workers posed by sleep loss, possibly leading to errors and injuries in the workplace. This association may also suggest that implementation of measures to increase sleep for night shift-workers could decrease risk-taking behaviours. Support (If Any): K23HL133186